Neisseria gonorrhoeae uses cellular proteins CXCL10 and IL8 to enhance HIV‐1 transmission across cervical mucosa. (11th April 2019) - Sanyal, Anwesha; Shen, Chengli; Ding, Ming; Reinhart, Todd A.; Chen, Yue; Sankapal, Soni; Gupta, Phalguni
Abstract : Problem: Neisseria gonorrhoeae (NG) infection has been shown to increase sexual transmission of HIV‐1. However, the mechanism of NG‐induced enhanced HIV‐1 transmission is unknown. Methods: (a) The cervical tissues were exposed to NG, and cytokine induction was monitored by measuring cytokine proteins in culture supernatants and cytokine mRNAs in tissues. (b) Transcription and replication of HIV‐1 in TZM‐bl, U1, and ACH2 cells were measured by Beta‐Gal activity and p24 proteins in the supernatant, respectively. (c) HIV‐1 transmission was assayed in an organ culture system by measuring transmitted HIV‐1 in supernatant and HIV‐1 gag mRNA in the tissues. (d) Transcriptome analysis was done using second generation sequencing. Results: (a) NG induced membrane ruffling of epithelial layer, caused migration of CD3+ cells to the intraepithelial region, and induced high levels of inflammatory cytokines IL‐1β and TNF‐α. (b) NG‐induced supernatants (NGIS) increased HIV‐1 transcription, induced HIV‐1 from latently infected cells, and increased transmission of HIV‐1 across cervical mucosa. (c) Transcriptome analysis of the epithelial layer of the tissues exposed to NG, and HIV‐1 showed significant upregulation of CXCL10 and IL8. IL‐1β increased the induction of CXCL10 and IL‐8 expression in cervical mucosa with a concomitant increase in HIV‐1 transmission. Conclusion: We present a model in which IL‐1β produced from cervical epithelium during NG exposure increases CXCL10 and IL8 in epithelia. This in turn causes upon HIV‐1 infection, the migration of HIV‐1 target cells toward the subepithelium, resulting in increased HIV‐1 transcription in the sub‐mucosa and subsequent enhancement of transmission across cervical mucosa.